Mga batang lansangan ngayon ([s.l.] Manhattan Asia Films., 2002)
The story of five orphans who have found a home away from home and family in each other. Although they do not live comfortable lives, they are still optimistic about life because of their faith in St. Michael, the archangel. They believe that their guardian angels are always by their side to watch over them and protect them from harm.
VCD
Joko Diaz, Bobby Andrews, Sunshine Dizon, Joanna Gonzales, Shaina Magdayao
Keywords: Street children; Drama; Feature films